Potentiometric and spectrophotometric determination of the stability constants of luteolin (3 ',4 ',5,7-tetrahydroxyflavone) complexes with aluminium(III) and iron(III) - (:unkn) unknown (POLSKIE TOWARZYSTWO CHEMICZNE-POLISH CHEMICAL SOC, 2003)
In this study, one determined stability constants of the complexes of luteolin with aluminium (III) and iron(III). Potentiometric methods of Calvin-Bjerrum and Irving-Rossotti, and spectrophotometric assay have been utilised. The evaluated protonation constants of the ligand were: logk(1) = 8.95, logk(2) = 8.10, and logk(3) = 6.85 at the 25degreesC. For the aluminium and iron complexes the subsequent logarithms of formation constants were found: for Al 17.50, 15.00, 4.75 and for iron: 19.60, 19.40, 17.82.
Keywords: luteolin; aluminium; iron; formation constant; protonation constants